Fire stopping - RIBA enterprises ([England : RIBA Enterprises)
This programme takes a look at principles of fire safety, along with common problems and solutions, but with a particular emphasis on passive fire protection that works through the compartmentation of buildings. General rules for compartmentation locations are covered, along with the issue of services penetrations - where inadequate detailing, finishing and maintenance can help fires spread. The programme also explores the fire resistance of particular materials (concrete, steel and timber), design problems that compromise fire safety in buildings.
DVD format.
Keywords: Construction industry -- Fires and fire prevention; Fireproofing